Physiotherapy and occupational therapy vs no therapy in mild to moderate Parkinson disease: a randomized clinical trial - Clarke, Carl E.; Patel, Smitaa; Ives, Natalie; Rick, Caroline E.; Dowling, Francis; Woolley, Rebecca; Wheatley, Keith; Walker, Marion F.; Sackley, Catherine Mary (American Medical Association, 2016)
IMPORTANCE It is unclear whether physiotherapy and occupational therapy are clinically effective and cost-effective in Parkinson disease (PD). OBJECTIVE To perform a large pragmatic randomized clinical trial to evaluate the clinical effectiveness of individualized physiotherapy and occupational therapy in PD. DESIGN, SETTING, AND PARTICIPANTS The PD REHAB Trial was a multicenter, open-label, parallel group, controlled efficacy trial. A total of 762 patients with mild to moderate PD were recruited from 38 sites across the United Kingdom. Recruitment took place between October 2009 and June 2012, with 15 months of follow-up. INTERVENTIONS Participants with limitations in activities of daily living (ADL) were randomized to physiotherapy and occupational therapy or no therapy. MAIN OUTCOMES AND MEASURES The primary outcome was the Nottingham Extended Activities of Daily Living (NEADL) Scale score at 3 months after randomization. Secondary outcomes were health-related quality of life (assessed by Parkinson Disease Questionnaire–39 and EuroQol-5D); adverse events; and caregiver quality of life. Outcomes were assessed before trial entry and then 3, 9, and 15 months after randomization. RESULTS Of the 762 patients included in the study (mean [SD] age, 70 [9.1] years), 381 received physiotherapy and occupational therapy and 381 received no therapy. At 3 months, there was no difference between groups in NEADL total score (difference, 0.5 points; 95%CI, −0.7 to 1.7; P = .41) or Parkinson Disease Questionnaire–39 summary index (0.007 points; 95%CI, −1.5 to 1.5; P = .99). The EuroQol-5D quotient was of borderline significance in favor of therapy (−0.03; 95%CI, −0.07 to −0.002; P = .04). The median therapist contact time was 4 visits of 58 minutes over 8 weeks. Repeated-measures analysis showed no difference in NEADL total score, but Parkinson Disease Questionnaire–39 summary index (diverging 1.6 points per annum; 95%CI, 0.47 to 2.62; P = .005) and EuroQol-5D score (0.02; 95%CI, 0.00007 to 0.03; P = .04) showed small differences in favor of therapy. There was no difference in adverse events. CONCLUSIONS AND RELEVANCE Physiotherapy and occupational therapy were not associated with immediate or medium-term clinically meaningful improvements in ADL or quality of life in mild to moderate PD. This evidence does not support the use of low-dose, patient-centered, goal-directed physiotherapy and occupational therapy in patients in the early stages of PD. Future research should explore the development and testing of more structured and intensive physical and occupational therapy programs in patients with all stages of PD.